Legacy and shockwaves: A spatial analysis of strengthening resilience of the power grid in Connecticut - Gallaher, Adam; Graziano, Marcello; Fiaschetti, Maurizio (Energy Policy, 2021)
Grid resilience and reliability are pivotal in the transition to low and zero carbon energy systems. Tree-trimming operations (TTOs) have become a pivotal tool for increasing the resilience power grids, especially in highly forested regions. Building on recent literature, we aim at assessing the temporal and spatial extents of the benefits that TTOs produce on the grid from three perspectives: the frequency, extent, and duration of outages. We use a unique dataset provided by Eversource Energy, New England's largest utility company, with outage events from 2009 to 2015. We employ spatial econometrics to investigate both the legacy and spatial extent of TTOs. Our results show TTOs benefits occur for all three metrics for at least 4 years, and benefits spillover to up to 2 km throughout the treated areas, with significant spatial spillovers across the state greater than direct effects. Implications lead to supporting TTOs as part of the hardening policies for utility companies, especially as home-based activities increase in importance in a post-COVID19 world. © 2021 Elsevier Ltd
12 citations (Crossref) [2023-10-31] https://discovery.ucl.ac.uk/id/eprint/10138230/ ; https://www.sciencedirect.com/science/article/pii/S0301421521004523
Keywords: COVID-19; Connecticut; Economics; Electric power transmission networks; Energy transitions; Low carbon; Outages; Power grids; Spatial analysis; Spatial extent; Spatial modelling; Statistics; Tree trimmings; Trimming; Trimming operations; United States; Utilities companies; Vegetation management; atmospheric electricity; data set; dept.mgt; econometrics; electricity; smart grid; spatiotemporal analysis; utility sector